MicroRNA-30a Suppresses the Activation of Hepatic Stellate Cells by Inhibiting Epithelial-to-Mesenchymal Transition - Jianjian Zheng; Wei Wang; Fujun Yu; Peihong Dong; Bicheng Chen; Meng-Tao Zhou (Cellular Physiology and Biochemistry, 2018)
Background/Aims: The activation of hepatic stellate cells (HSCs) is considered as a pivotal event in liver fibrosis and epithelial-mesenchymal transition (EMT) process has been reported to be involved in HSC activation. It is known that microRNAs (miRNAs) play a pro-fibrotic or anti-fibrotic role in HSC activation. Recently, emerging studies show that miR-30a is down-regulated in human cancers and over-expression of miR-30a inhibits tumor growth and invasion via suppressing EMT process. However, whether miR-30a could regulate EMT process in HSC activation is still unclear. Methods: miR-30a expression was quantified using real-time PCR in carbon tetrachloride (CCl4)-induced rat liver fibrosis, activated HSCs and patients with cirrhosis. Roles of miR-30a in liver fibrosis in vivo and in vitro were also analyzed. Luciferase activity assays were performed to examine the binding of miR-30a to the 3′-untranslated region of snail family transcriptional repressor 1 (Snai1). Results: miR-30a was down-regulated in human cirrhotic tissues. In CCl4 rats, reduced miR-30a was found in fibrotic liver tissues as well as isolated HSCs. There was a significant reduction in miR-30a in primary HSCs during culture days. miR-30a over-expression resulted in the suppression of CCl4-induced liver fibrosis. Restoration of miR-30a led to the inhibition of HSC activation including cell proliferation, α-SMA and collagen expression. Notably, miR-30a inhibited EMT process, with a reduction in TGF-β1 and Vimentin as well as an increase in GFAP and E-cadherin. miR-30a induced a significant reduction in Snai1 protein expression when compared with the control. Interestingly, Snail protein expression was increased during liver fibrosis, indicating that there may be a negative correlation between miR-30a level and Snai1 protein expression. Further studies demonstrated that Snai1 was a target of miR-30a. Conclusion: Our results suggest that miR-30a inhibits EMT process, at least in part, via reduction of Snai1, leading to the suppression of HSC activation in liver fibrosis.